Improving combination antiretroviral therapy by targeting HIV-1 gene transcription. (1st November 2016) - Le Douce, Valentin; Ait-Amar, Amina; Forouzan far, Faezeh; Fahmi, Faiza; Quiel, Jose; El Mekdad, Hala; Daouad, Fadoua; Marban, Céline; Rohr, Olivier; Schwartz, Christian
ABSTRACT: Introduction : Combination Antiretroviral Therapy (cART) has not allowed the cure of HIV. The main obstacle to HIV eradication is the existence of quiescent reservoirs. Several other limitations of cART have been described, such as strict life-long treatment and high costs, restricting it to Western countries, as well as the development of multidrug resistance. Given these limitations and the impetus to find a cure, the development of new treatments is necessary. Areas covered : In this review, we discuss the current status of several efficient molecules able to suppress HIV gene transcription, including NF-kB and Tat inhibitors. We also assess the potential of new proteins belonging to the intriguing DING family, which have been reported to have potential anti-HIV-1 activity by inhibiting HIV gene transcription. Expert opinion : Targeting HIV-1 gene transcription is an alternative approach, which could overcome cART-related issues, such as the emergence of multidrug resistance. Improving cART will rely on the identification and characterization of new actors inhibiting HIV-1 transcription. Combining such efforts with the use of new technologies, the development of new models for preclinical studies, and improvement in drug delivery will considerably reduce drug toxicity and thus increase patient adherence.